Studi Literatur Pengaruh Penambahan Arang Tempurung Kelapa terhadap Inovasi Pemanfaatan Char Gasifikasi Batubara sebagai Bahan Bakar Ramah Lingkungan - Aria Yopianita (Jurnal Studi Inovasi, 2022)
Coal reserves in Indonesia are estimated at around 26 billion tons and will still be primary energy until 2050. This makes the use of green coal and clean energy an urgent homework. One of the uses of coal is coal gasification. From the results of coal gasification, a by-product is obtained, namely char. In this char characterization, it is found that char has an increase in fixed carbon and GCV values as well as a significant decrease in sulfur content. This makes char potentially a raw material for environmentally friendly solid fuels (briquettes). The addition of biomass in the form of coconut shell charcoal is expected to increase the calorific value and allow ignition from low temperatures which can then save the time and energy needed for briquetting ignition and maintain the combustion rate. Therefore, as an initial study, it is necessary to study literature from previous studies as the basis for the initial hypothesis of the addition of coconut shell charcoal in the manufacture of briquettes with the main raw material of char from coal gasification